Komposisi Pupuk Cair Dari Berbagai Markah Yang Beredar Di Indinesia - Rahayu S Rofienda (Balai Besar Kimia dan Kemasan, 1989)
Liguid fertilizer of six trade marks which is sold in Indonesian market has been tested to determine its composition.The results indicate that most of those samples can be classified as NPK fertilizer. It seen also that micronutrition contents of the samples being tested are very low;